2017
DOI: 10.1080/10903127.2016.1258098
|View full text |Cite
|
Sign up to set email alerts
|

Hot and Cold Drugs: National Park Service Medication Stability at the Extremes of Temperature

Abstract: We recommend that EMS providers replace atropine, naloxone, diphenhydramine, fentanyl, and midazolam frequently if they are practicing in low call volume or high-temperature environments. Further studies will be needed to determine if re-dosing midazolam, naloxone, and atropine is the appropriate clinical strategy in this setting if adequate clinical effect is not reached with a single dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In addition, medication required to be stored at “room temperature” may still be affected given the high environmental temperatures during the pilgrimage. Extreme temperatures cause the degradation of medications, which may change their pharmacological characteristics, reduce their potency and efficacy or result in compromised or toxic products, leading to adverse health outcomes [ 1 , 2 , 3 , 4 , 20 ]. Consequently, the appropriate handling and storage of medication among pilgrims during Hajj are of public health importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, medication required to be stored at “room temperature” may still be affected given the high environmental temperatures during the pilgrimage. Extreme temperatures cause the degradation of medications, which may change their pharmacological characteristics, reduce their potency and efficacy or result in compromised or toxic products, leading to adverse health outcomes [ 1 , 2 , 3 , 4 , 20 ]. Consequently, the appropriate handling and storage of medication among pilgrims during Hajj are of public health importance.…”
Section: Discussionmentioning
confidence: 99%
“…Humidity and light are additional environmental factors that can affect medications. If medications are significantly degraded, this may affect their clinical effectiveness, which may result in changes in dosage, storage conditions, or how often they need to be replaced [ 3 , 4 ]. For most drugs, manufacturers assure a potency of 90–110% for a specified period, but only if stored as recommended [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Armenian et al also observed naloxone hydrochloride exhibits temperature-dependent degradation [15]. Naloxone hydrochloride ampoules were subject to several conditions ( sustained temperatures of − 20 °C, + 45 °C, or alternating weekly between the two) for 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although temperatures as high as 70 °C have been evaluated, internal vehicle temperatures can reach up to 80 °C [12, 13]. Several studies also assessed the effect of temperature fluctuations from extreme cold to heat (− 20 °C to 70 °C; − 6 °C to 54 °C; − 20 °C to 45 °C); however, it is unlikely that these conditions would be experienced within the span of a single day, should a THN kit be left within a vehicle [12, 14, 15]. These studies also did not investigate the association of stability with the duration of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures can range from -20ºC in mountainous regions to 40ºC in deserts. 10,11 The time constraints of TXA administration necessitate that it be readily available within these conditions. Multiple studies have already shown large fluctuations in storage temperatures of prehospital medications.…”
Section: Introductionmentioning
confidence: 99%